Parosteal osteosarcoma with myocardial metastasis 13 years after follow-up - Santos-Machado,Telma M. (2003)
PURPOSE: To report the case of a woman with a diagnosis of grade II (low grade) parosteal osteosarcoma with the occurrence of myocardial metastasis 13 years after resection, and to present a review of the existing literature on the subject. METHODS: Description of the case and review of the literature. CONCLUSION: The review leads to the conclusion that the occurrence of metastasis from parosteal osteosarcoma can occur in up to 38% of the cases, in spite of its relatively low aggressiveness. However, myocardial metastasis of a parosteal osteosarcoma is an event that was not found in the literature.